IDENTIFIKASI DAN INTENSITAS PARASIT PADA LOBSTER AIR LAUT (PANULIRUS SP.) : Identification and Intensity of Parasites in Sea Water Lobster (Panulirus sp.) - Abid Azomi; Kurniawati Kurniawati; Aryani Rahmawati; L.A.T.T.W. Sukmaring Kalih (Yayasan Al-Amin Qalbu, 2023)
The aims of this study were to identify parasites on sea crayfish (panulirus sp) and to determine the intensity of parasitic attacks on sea crayfish (panulirus sp). This research was conducted at the Fish Quarantine Center for Quality Control and Safety of Class II Fishery Products in Mataram. The method used in this study is the Descriptive Method, which is a method that provides a complete, systematic and factual description of data or activities that are not limited to data collection and compilation which includes analysis and discussion of data. This study took 7 samples and during the examination there were 5 samples that tested positive for parasite infection and 2 tested negative. The results of the research or examination showed that the invading parasite panulirus sp was found on the external part (ectoparasites), while examination on the internal part (endoparasites) could not be carried out due to a lack of supporting tools and materials. The parasites that were found on the external part included Octolasmis. sp., Nematoda and Chilodonella sp. The results of calculating the intensity and prevalence of parasites on sea crayfish (panulirus sp) are very diverse, namely Octolasmis sp. 23.5%, Chilodonella sp. 23% and Nematodes 13%. The results of the valence calculation show Octolasmis. sp., and Chilodonella sp. have the same prevalence rate of 28.57% while Nematodes have the lowest prevalence rate of 14.28%.